2018
DOI: 10.1089/lap.2017.0665
|View full text |Cite
|
Sign up to set email alerts
|

Cryoanalgesia in Patients Undergoing Nuss Repair of Pectus Excavatum: Technique Modification and Early Results

Abstract: Our technique modification simplifies previously described approaches to intercostal nerve cryoablation. Patients undergoing this adjunct benefit with less PNR and a faster discharge time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 23 publications
2
30
1
Order By: Relevance
“…Parrado et al (16) compared post-operative consumption of morphine in three different groups (cryoanalgesia, epidural, and multimodal analgesia) and they found that opioid consumption was lower in cryoanalgesia group (237 mg). In our pilot study the average value of total opioid consumption was 7.5 mg in line with results of Morikawa et al (17). Our patients showed a length of stay of 2.4 days, in line with other studies [1.9 days in Grave et al's (11), 2.2 ± 0.4 in Morikawa et al's (17)].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Parrado et al (16) compared post-operative consumption of morphine in three different groups (cryoanalgesia, epidural, and multimodal analgesia) and they found that opioid consumption was lower in cryoanalgesia group (237 mg). In our pilot study the average value of total opioid consumption was 7.5 mg in line with results of Morikawa et al (17). Our patients showed a length of stay of 2.4 days, in line with other studies [1.9 days in Grave et al's (11), 2.2 ± 0.4 in Morikawa et al's (17)].…”
Section: Discussionsupporting
confidence: 92%
“…In our pilot study the average value of total opioid consumption was 7.5 mg in line with results of Morikawa et al (17). Our patients showed a length of stay of 2.4 days, in line with other studies [1.9 days in Grave et al's (11), 2.2 ± 0.4 in Morikawa et al's (17)].…”
Section: Discussionsupporting
confidence: 92%
“…Five subgroups of patients were identified: pectus excavatum (nine studies); thoracotomy (eight studies); post-thoracotomy pain syndrome (PTPS; three studies); chest wall pain from malignancy (two studies); and traumatic rib fractures (two studies). In 2018, Morikawa et al 7 performed a retrospective review comparing children who received cryoneurolysis (n=6) during Nuss repair to those who did not (n=13). Patients who underwent cryoneurolysis were discharged faster (2.2 vs. 3.7 days, p=0.01) and required lower narcotic doses (6.4 vs. 17.9 morphine equivalents (ME), p=0.05).…”
Section: Resultsmentioning
confidence: 99%
“…There were no differences in self-reported pain scores for the first 3 days post-operatively, but there was some neuropathic pain in the cryoanalgesia group in the months that followed. Morikawa et al [524] examined the use of intercostal nerve cryoanalgesia (n = 6 patients) supplementing the use of standard pharmacological pain relief post-thoracotomy (n = 13 patients with no cryoanalgesia). Pain scores were not different, but the patients supplemented with intercostal nerve cryoanalgesia had a lower opioid requirement and were discharged on average 1 day earlier.…”
Section: Cryoanalgesiamentioning
confidence: 99%